Safety and efficacy of laxatives after major abdominal surgery: systematic review and meta-analysis. Issue 4 (27th May 2020) - Dudi-Venkata, N N; Seow, W; Kroon, H M; Bedrikovetski, S; Moore, J W; Thomas, M L; Sammour, T
Abstract: Background: Recovery of gastrointestinal function is often delayed after major abdominal surgery, leading to postoperative ileus (POI). Enhanced recovery protocols recommend laxatives to reduce the duration of POI, but evidence is unclear. This systematic review aimed to assess the safety and efficacy of laxative use after major abdominal surgery. Methods: Ovid MEDLINE, Embase, Cochrane Library and PubMed databases were searched from inception to May 2019 to identify eligible RCTs focused on elective open or minimally invasive major abdominal surgery. The primary outcome was time taken to passage of stool. Secondary outcomes were time taken to tolerance of diet, time taken to flatus, length of hospital stay, postoperative complications and readmission to hospital. Results: Five RCTs with a total of 416 patients were included. Laxatives reduced the time to passage of stool (mean difference (MD) −0·83 (95 per cent c.i. −1·39 to −0·26) days; P = 0·004), but there was significant heterogeneity between studies for this outcome measure. There was no difference in time to passage of flatus (MD −0·17 (−0·59 to 0·25) days; P = 0·432), time to tolerance of diet (MD −0·01 (−0·12 to 0·10) days; P = 0·865) or length of hospital stay (MD 0·01(−1·36 to 1·38) days; P = 0·992). There were insufficient data available on postoperative complications for meta-analysis. Conclusion: Routine postoperative laxative use after major abdominal surgery may result in earlier passage of stool but does not influence other postoperative recovery parameters. Better data are required for postoperative complications and validated outcome measures. Graphical Abstract: Routine postoperative laxative use after major abdominal surgery may result in earlier passage of stool, but does not influence other postoperative recovery parameters. Better data are required for postoperative complications and validated outcome measures. Laxatives after major abdominal surgery